Characteristics and associated risk factors of diverticular disease assessed by magnetic resonance imaging in subjects from a Western general population - Storz, Corinna; Schlett, Christopher L. (European radiology, 2019)
ObjectivesDiverticular disease represents an increasing pathology and healthcare burden worldwide. Our aim was to study the prevalence, extent and distribution of asymptomatic diverticular disease assessed by magnetic resonance imaging (MRI) in a sample of a Western population.MethodsSubjects from a population-based cohort study who underwent 3-T MRI were analyzed for the prevalence and extent of diverticula of the colon using an isotropic VIBE-Dixon gradient-echo sequence. The extent of diverticular disease was categorized according to the number of diverticula in each colonic segment. Univariate and adjusted analyses were performed to assess associated characteristics and risk factors.ResultsAmong 393 subjects included in the analysis (56.4 ± 9.2 years, 57.5% males), 164 (42%) had diverticular disease, with the highest prevalence in the left-sided colonic segments (93% diverticular disease in the descending and sigmoid segment). Subjects with advanced diverticular disease were older (62.1 vs. 54.4 years) and had a higher body mass index (BMI), LDL cholesterol levels and systolic blood pressure (30.2 ± 5.1 vs. 27.8 ± 4.9 kg/m2, 149.8 ± 29.3 vs. 135.2 ± 32.9 mg/dl and 128.2 ± 14.1 vs. 118.4 ± 16.1 mmHg, respectively; all p > 0.003) compared with subjects without diverticular disease. In contrast, no significant correlation could be found for gender, physical activity, smoking status and alcohol consumption (all p > 0.31). Intra-rater reliability was excellent for all colonic segments (intra-class correlation [ICC] = 0.99-1.00), and inter-rater reliability was excellent for left- and right-sided colonic segments (ICC = 0.84-0.97).ConclusionsThese findings provide insights into the disease mechanism of asymptomatic diverticular disease and may help to improve prevention of diverticulosis and its associated complications.Key Points • Overall prevalence of asymptomatic diverticular disease assessed by MRI was 42%, affecting predominantly the left-sided colon. • Asymptomatic diverticular disease was associated with age and cardiometabolic risk factors. • Magnetic resonance imaging reveals insights into the pathophysiologic mechanism of asymptomatic diverticular disease.